ABHRAKA BHASMA A BOON OF AYURVEDA TO MANKIND: A REVIEW - Prashant Sakharam Bhokardankar; Sandeep Gorakh Mane; Bhupendra Prakash Khairanar (International Journal of Ayurveda and Pharma Research, 2019)
Abhraka bhasma is a popular Rasashastra medicine in Ayurveda stream. It is basically herbomineral preparation used by all Ayurvedic Vaidyas since long time. Abhraka is basically Mica (Biotite). Bhasma is nothing but incinerated ash. Rasashastra is an Indian metallurgy which deals with several minerals and herbomineral preparations specially Bhasmas. There are several popular bhasmas in Ayurveda but there is great demand of this Bhasma in Ayurvedic vaidyas. Use of this bhasma is in multiple disorders, so could be consider as a major Ayurvedic drug. Published details scientific literature on Abhraka bhasma by various research scholars, internet & pharmacopeias were reviewed. The review was done to find physicochemical characteristics as well as standardization studies done on Abhraka bhasma. Also attempt is to made to find scientific studies done on Abhraka bhasma. Need of hour to evaluate its efficacy value as potential Ayurvedic drug in various disorders. As well as importance of Abhraka bhasma as an evidence-based drug. Review of literatures and scientific studies of Abhraka bhasma clearly indicate that there are lot of studies is done on Abhraka bhasma’s specially it’s physicochemical characteristics, standardization as well as it’s therapeutic uses. Abhraka bhasma is indicated in several ailments like Diabetes, Asthma, Paralysis, Neurological condition, Tuberculosis and Acid peptic diseases.